School engagement and burnout in a sample of Brazilian students - Zucoloto, Miriane Lucindo [UNESP] (2016)
Objective Some studies have suggested that school engagement can be an ally in the prevention of psychosocial and occupational risks, to which students are exposed daily. The aim of this study is to estimate the impact of emotional, behavioral, and cognitive engagement on burnout syndrome among pharmacy undergraduate students. Methods A total of 363 students enrolled in the pharmacy undergraduate program in the College of Pharmaceutical Sciences at Sao Paulo State University's Araraquara Campus (UNESP) participated, 78.0% of whom were female. Mean age was 20.3 (SD = 2.7) years. The Maslach Burnout Inventory for students (MBI-SS) and the University Students School Engagement Inventory (USEI) were used. Confirmatory factor analysis was performed to assess the psychometric properties of the instruments. The data were included in a structural equation model in which burnout was considered the central construct. The impact of school engagement on burnout was based on the statistical significance of causal paths (β) evaluated by z tests (α = 5%). Results The psychometric properties of the MBI-SS and USEI were adequate and the structural model also presented an adequate fit. Behavioral engagement (β = −0.56) and the emotional engagement (β = −0.71) explained 81.0% of burnout variability in the sample. Cognitive engagement was not found to contribute significantly. This data provides evidence of the impact of school engagement on burnout that can be used by educators and policymakers in charge of educational process. Conclusion School engagement presented inverse and significant influence on burnout syndrome among pharmacy students.